2002
DOI: 10.1002/rsa.10070
|View full text |Cite
|
Sign up to set email alerts
|

How many random edges make a dense graph hamiltonian?

Abstract: This paper investigates the number of random edges required to add to an arbitrary dense graph in order to make the resulting graph hamiltonian with high probability. Adding Θ(n) random edges is both necessary and sufficient to ensure this for all such dense graphs. If, however, the original graph contains no large independent set, then many fewer random edges are required. We prove a similar result for directed graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
165
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(172 citation statements)
references
References 6 publications
7
165
0
Order By: Relevance
“…We now change the setup in the following way, as first suggested by Bohman, Frieze and Martin [6] (though they worked with G(n, m) instead of G(n, p)). For α ∈ (0, 1), let G α be any graph with minimum degree at least αn and reveal more edges within the graph independently at random with probability p. That is, we study the properties of G α ∪ G(n, p).…”
Section: Randomly Perturbed Graphsmentioning
confidence: 99%
See 1 more Smart Citation
“…We now change the setup in the following way, as first suggested by Bohman, Frieze and Martin [6] (though they worked with G(n, m) instead of G(n, p)). For α ∈ (0, 1), let G α be any graph with minimum degree at least αn and reveal more edges within the graph independently at random with probability p. That is, we study the properties of G α ∪ G(n, p).…”
Section: Randomly Perturbed Graphsmentioning
confidence: 99%
“…For α ∈ (0, 1/2) Bohman, Frieze and Martin [6] showed that if p = ω(1/n) then whp there is a Hamilton cycle in G α ∪ G(n, p) for any G α . Furthermore, this is optimal, as for p = o(1/n) there are graphs G α such that G α ∪ G(n, p) is not Hamiltonian whp.…”
Section: Randomly Perturbed Graphsmentioning
confidence: 99%
“…For example, Bohman, Frieze and Martin [2] considered graphs of the form G = H + R where H is arbitrary, but with high minimum degree and R is random. In this section we consider graphs of the form G = R − H where R is random and H is an arbitrary subset of R, subject to some restrictions.…”
Section: Robustness Of Hamiltonicitymentioning
confidence: 99%
“…The random graph model GH,m was first introduced by Bohman, Frieze, and Martin . It can be considered as an extension of the Erdős‐Rényi model, which we can retrieve from GH,m by setting Hgoodbreakinfix=.…”
Section: Introductionmentioning
confidence: 99%
“…How many are needed so that the result is a graph that satisfies property scriptP w.h.p . In , they study the case where scriptG is the set of graphs of minimum degree δngoodbreakinfix,δgoodbreakinfix>0 and scriptP is the property of a graph having a Hamilton cycle. They show that a linear number of random edges suffices to make any member of scriptG Hamiltonian w.h.p.…”
Section: Introductionmentioning
confidence: 99%